Cloning and characterisation of JAZ gene family in Hevea brasiliensis. (8th December 2014) - Hong, H.; Xiao, H.; Yuan, H.; Zhai, J.; Huang, X.; Peeters, T.
Abstract Mechanical wounding or treatment with exogenous jasmonates (JA) induces differentiation of the laticifer in Hevea brasiliensis. JA is a key signal for latex biosynthesis and wounding response in the rubber tree. Identification of JAZ (jasmonate ZIM‐domain) family of proteins that repress JA responses has facilitated rapid progress in understanding how this lipid‐derived hormone controls gene expression and related physiological processes in plants. In this work, the full‐length cDNAs of six JAZ genes were cloned from H. brasiliensis (termed HbJAZ). These HbJAZ have different lengths and sequence diversity, but all of them contain Jas and ZIM domains, and two of them contain an ERF‐associated amphiphilic repression (EAR) motif in the N‐terminal. Real‐time RT‐PCR analyses revealed that HbJAZ have different expression patterns and tissue specificity. Four HbJAZ were up‐regulated, one was down‐regulated, while two were less effected by rubber tapping treatment, suggesting that they might play distinct roles in the wounding response. A yeast two‐hybrid assay revealed that HbJAZ proteins interact with each other to form homologous or heterogeneous dimer complexes, indicating that the HbJAZ proteins may expand their function through diverse JAZ–JAZ interactions. This work lays a foundation for identification of the JA signalling pathway and molecular mechanisms of latex biosynthesis in rubber trees.